2009
DOI: 10.1002/hyp.7423
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of stream nitrate sources and flow pathways during stormflows on urban, forest and agricultural watersheds in central Pennsylvania, USA

Abstract: Abstract:Understanding the influence of storm events on nitrate (NO 3 ) dynamics is important for efficiently managing NO 3 pollution. In this study, five sites representing a downstream progression of forested uplands underlain by resistant sandstone to karst lowlands with agricultural, urban and mixed land-use were established in Spring Creek, a 201 km 2 mixed land-use watershed in central Pennsylvania, USA. At each site, stream water was monitored during six storm events in 2005 to assess changes in stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 57 publications
10
84
0
Order By: Relevance
“…Assuming that 50% of all pervious areas are fertilized, 5 this would be the equivalent of 69 to 130 kg N ha −1 y −1 input via fertilization, an order of magnitude larger than estimates of total annual N deposition of <6 to 18 kg/ha. 45,46 As in previous studies, 4,20,47,48 we found that f atm in urban stormwater was high, averaging 34%. The contribution of NO 3 − to total NO 3 − atm export from watersheds ranged from 4 to 53% across all observed events ( Figure 5), and observations of f atm for individual samples within events ranged much more widely (0 to 80% over all samples).…”
Section: ■ Results and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Assuming that 50% of all pervious areas are fertilized, 5 this would be the equivalent of 69 to 130 kg N ha −1 y −1 input via fertilization, an order of magnitude larger than estimates of total annual N deposition of <6 to 18 kg/ha. 45,46 As in previous studies, 4,20,47,48 we found that f atm in urban stormwater was high, averaging 34%. The contribution of NO 3 − to total NO 3 − atm export from watersheds ranged from 4 to 53% across all observed events ( Figure 5), and observations of f atm for individual samples within events ranged much more widely (0 to 80% over all samples).…”
Section: ■ Results and Discussionsupporting
confidence: 84%
“…At the two surface-drained watersheds there were significant negative correlations between δ 15 N and δ 18 O (ρ = −0.87, p < 0.05 and ρ = −0.63, p < 0.05) during the 13 December 2011 event. These results support findings from other studies suggesting that variation in NO 3 − isotopes in urban 4,20,47,48,50,53 and nonurban 48,49 waters is primarily a result of the mixing of sources rather than biogeochemical processing along flowpaths during runoff events. Across a range of land uses, isotopic evidence of denitrification at the watershed scale has only been documented during baseflow conditions and is largely limited to agricultural watersheds.…”
Section: Microbially Nitrified Nosupporting
confidence: 91%
“…When compared with the TN concentrations of rivers and lakes in the Beijing metropolitan area in 2003, at which point they were all below 2 mg $L -1 [17], TN concentrations showed an increasing trend. The TN concentrations reported in this study are higher than those in the Taihu lake region [26], in the Haicheng river basin [27]and in the Beijiang river in south China [28], but close to the TN level of the Thames river in the UK [29], and of stream water in Pennsylvania, USA [30]. These increasing TN concentrations may be due to intensification of human activities caused by urbanization, and agrees with other studies which have shown that urbanization results in elevated TN and NO -3 -N concentrations in watersheds in developing areas [31,32], and that urbanization soon takes over as the major source of nitrogen in urban freshwater ecosystems [27].…”
Section: Characteristics Of Nitrogen Pollutionsupporting
confidence: 45%
“…Atmospheric nitrogen deposition rates for Beijing have been estimated at 75.13 mg$m -2 , and, from June to September 2009, showed a significantly increasing trend [51]. Other authors have reported that direct runoff of atmospheric NO -3 -N, mobilized from impervious surfaces, is an important source of NO -3 -N in urban watersheds during storm events [1,30,52]. In Beijing, atmospheric nitrogen deposition may account for a larger proportion of nitrogen pollution in the upper stream region relative to the downstream reaches, where the contribution from sewage was higher.…”
Section: -N=c1mentioning
confidence: 99%
“…The hydrologic cycle is a key driver of Nr loss to the environment and surface waters in particular are sites of significant Nr transport and transformation (Carpenter et al 1998, Seitzinger et al 2002. Streams with watersheds that are dominated by agricultural land uses often transport significant amounts of N because N application rates are so high (Howden et al 2011, Buda andDeWalle 2009). During base flows, N transport via the hydrologic cycle is typically in the form of NO 3 -, which is highly soluble (Howden et al 2011).…”
Section: Nr Transport Via the Hydrologic Cyclementioning
confidence: 99%